2018
DOI: 10.1007/s12029-018-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes in Patients with Metastatic Neuroendocrine Tumors: a Retrospective Analysis of a Community Oncology Database

Abstract: While potentially confounded by the high number of patients with other or unknown tumor locations, this retrospective study of patients in a US community oncology setting identified the importance of awareness of tumor grade and tumor location at diagnosis, as these were direct correlates of PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Although multiple series [22–25] have documented the use of SSAs among patients with G3 NETs, this is, to our knowledge, the first study to formally report the survival outcomes associated with SSAs in an albeit small cohort of patients with well‐differentiated, G3 panNETs. The rationale to treat patients with G3 panNETs with somatostatin‐based therapies relies on the expression of somatostatin receptors, which has been described in small series to occur in up to 80% of G3 GEP‐NETs [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple series [22–25] have documented the use of SSAs among patients with G3 NETs, this is, to our knowledge, the first study to formally report the survival outcomes associated with SSAs in an albeit small cohort of patients with well‐differentiated, G3 panNETs. The rationale to treat patients with G3 panNETs with somatostatin‐based therapies relies on the expression of somatostatin receptors, which has been described in small series to occur in up to 80% of G3 GEP‐NETs [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, a relatively high proportion of patients (64%) had CS at the time of GI NET diagnosis. Prior studies have reported a wide range of proportions of patients with NET and CS, ranging from 3% to 74% across studies . Halperin et al reported that 19% of those diagnosed with NET between 2000 and 2011 in SEER‐Medicare had CS within 6 months of NET diagnosis, with the percentage increasing over time .…”
Section: Discussionmentioning
confidence: 99%
“…In that study, CS was also shown to be associated with advanced disease , which was an eligibility requirement for patients in the current study. Using a U.S. cancer database, Fisher et al reported 43% of patients with metastatic NET had some CS symptoms . Pulgar et al reported 57% of patients with metastatic GEP NET had CS symptoms in an analysis of U.S. oncology electronic health records .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several publications describing real-world treatment patterns for GEP-NET [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The majority of these studies are North American (mainly US), while a few are from Europe and other continents.…”
Section: Introductionmentioning
confidence: 99%